2020
DOI: 10.21203/rs.2.20508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Qualitative research of informal caregivers’ personal experiences caring for older adults with mental disorders in Lithuania: A phenomenological approach

Abstract: Background In many communities around the world, informal caregivers of older adults with mental disorders (such as dementia) represent an essential, yet often underappreciated, source of long-term care. The present study aimed to determine the personal experiences of such caregivers, which could be instrumental for developing means of improving the quality of care for both care receivers and their informal caregivers.Methods Five semi-structured focus-group discussions were held. The participants (n = 31) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent qualitative study on Lithuanian informal caregivers reported that some caregivers experienced difficulty in communicating with the healthcare professionals. 22 Studies in other countries have also found that carers experience dissatisfaction with the healthcare providers in terms of information provision, treatment optimisation, involvement of the caregiver and management of caregivers’ own health. 34 As a solution, additional training could be offered to the professionals about guiding and supporting informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent qualitative study on Lithuanian informal caregivers reported that some caregivers experienced difficulty in communicating with the healthcare professionals. 22 Studies in other countries have also found that carers experience dissatisfaction with the healthcare providers in terms of information provision, treatment optimisation, involvement of the caregiver and management of caregivers’ own health. 34 As a solution, additional training could be offered to the professionals about guiding and supporting informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“… 20 The available literature regarding Lithuanian informal caregivers’ needs is very limited and is mostly based on small scale qualitative findings. 22 23 Some of the needs that were outlined were the need for support regarding care receiver’s as well as own well-being, 23 opportunity for formalised training, 24 flexible working conditions 20 and more professional support and respite services. 25 Although it is evident that Lithuanian informal caregivers experience certain strains, more data are needed for gaining knowledge about their basic characteristics and evaluating their challenges so that the following guidelines regarding suitable support options could be proposed.…”
Section: Introductionmentioning
confidence: 99%